Early handedness in infancy predicts language ability in toddlers - Nelson, Eliza L. (2013)
Researchers have long been interested in the relationship between handedness and language in development. However, traditional handedness studies using single age groups, small samples, or too few measurement time points have not capitalized on individual variability and may have masked two recently identified patterns in infants: those with a consistent hand-use preference and those with an inconsistent preference. In this study, we asked whether a consistent infant hand-use preference is related to later language ability. We assessed handedness in 38 children at monthly intervals from 6–14 months (infant visits) and again from 18–24 months (toddler visits). We found that consistent right-handedness during infancy was associated with advanced language skills at 24 months as measured by the Bayley-III(®). Children who were not lateralized as infants, but became right-handed or left-handed as toddlers, had typical language scores. Neither timing nor direction of lateralization was related to cognitive or general motor skills. This study builds on previous literature linking right-handedness and language during the first 2 years of life.